Gender empowerment and energy access: evidence from seven countries. (1st April 2023) - Chandrasekaran, Maya; Krishnapriya, P P; Jeuland, Marc; Pattanayak, Subhrendu K
Abstract: Gender equity is connected to modern energy services in many ways, but quantitative empirical work on these connections is limited. We examine the relationship between a multi-dimensional measure of women's empowerment and access to improved cookstoves, clean fuels, and electricity. We use the World Bank Multi-Tier Framework survey datasets from seven countries that include almost 25 000 households in Africa and Asia. First, we apply principal component analysis to construct a household level empowerment index, using data on women's education, credit access, social capital, mobility, and employment. Then, we use simple regression analysis to study the correlation between empowerment and energy access at the household level. We find a positive association between the women's empowerment index and energy access variables, though this household pattern does not hold across all countries and contexts. While we do not claim that these relationships are causal, to our knowledge this is a fresh analysis of how the empowerment of women is differentially correlated with household energy access across geographies and technologies. Thus, our analysis provides a first step to further work aimed at clarifying gender-energy linkages.